Assessment of the ameliorative roles of Vitamin E on the histopathology of Clarias Gariepinus (Burchell, 1822) fingerlings exposed to lead nitrate - Samuel PO; Arimoro FO; Ayanwale AV; Mohammad HL (Global Journal of Zoology - Peertechz Publications, 2022)
Pollution of aquatic ecosystems is constantly increasing with the increase in anthropogenic activities all over the world with negative effects on the constituent biota. The current study addressed the possibility of remedying the effects posed to the tissues of Clarias gariepinus fingerlings (3-11g initial weight) exposed to lead nitrate over a 12 week period. The treatment groups were Pb only and PbVE (Pb+vitamin E) with T1-T4 and replicate in each case. The sub-lethal treatments of lead nitrate concentrations are as follow: 00 (control), 26mg/L (T1), 44mg/L (T2), 61mg/L (T3) and 79mg/L (T4). 26mg/L concentration of the vitamin was applied to every treatment and replicate of the PbVE group. At the end of the exposure period, gills, liver, and kidneys were excised from the samples and preserved in 10% formalin for histopathological analyses. From the results; the livers of the samples of C. gariepinus exposed to sub-lethal concentration of Pb only group displayed aggregation and lumping together of the hepatocytes, massive necrosis and shattering of the hepatocytes, vacoulation with greater severity as the concentration increased. The samples of PbVE treatment group showed preserved hepatocytes, reduced aggregation and vacoulation of the cells, gradual recovery of the cell nucleus and cytoplasm, normal tissue architecture, and hepatocytes similar to control samples in T1-T3. In the kidneys of Pb only group, there were massive necrosis and vacoulation, shattering of cells, tissue edema, and massive lumping of cells together, especially in higher concentrations. The PbVE treatments displayed reduced necrosis and cells aggregating together coupled with reduced vacoulation, preserved cells, and cells with cytoplasm returning to normal. But these were not sustained in the highest concentration. In the gills of the Pb only group, there was rarefied gill filament with ruptured lamellae, shattered gill arch, and filaments ruptured primary and secondary lamellae with greater severity in higher concentrations. The PbVE group displayed how the gill arch and filaments with the primary and secondary lamellae were gradually restored to a certain extent similar to the control. In all the organs the alteration and amelioration of the architecture were concentration-dependent. Therefore, a proportionate concentration of the vitamin can facilitate faster tissue damage recovery in heavy metal exposure.